The Influence of Principal Leadership, Organizational Culture, Teacher Performance and Teacher Work Motivation on the Quality of Education - Basuki Basuki; Istiatin Istiatin; Sudarwati Sudarwati (STIE PENA, 2026)
This study aims to determine the simultaneous (simultaneous) and partial influence of the variables of Principal Leadership, Organizational Culture, Teacher Performance and Teacher Work Motivation on the Quality of Education at PKBM Ibnu Abbas Klaten. This research method uses a quantitative research design. The population in this study were all Teachers and Administrative Staff working at PKBM Ibnu Abbas Klaten, totaling 46 people. The sampling technique used in this study was a census technique with a sample of 46 respondents. Data collection using a questionnaire. The data analysis technique used statistical analysis, namely multiple linear regression tests, F tests, t tests, and coefficients of determination. The results of the study indicate that Principal Leadership, Organizational Culture, Teacher Performance and Work Motivation simultaneously and significantly influence the Quality of Education at PKBM Ibnu Abbas Klaten. Suggestions from this study, PKBM Ibnu Abbas Klaten should continue to maintain the quality of principal leadership, performance quality, positive culture and teacher work motivation through the support of continuous professional development, coaching and periodic capacity building. These efforts are expected to maintain and improve the quality of education at PKBM Ibnu Abbas Klaten. Keywords: Principal Leadership, Organizational Culture, Teacher Performance and Work Motivation, Quality of Education